Effect of the Irish Civil War 1922-1923 on suicide rates in Ireland: a retrospective investigation of the archives of the registrar-general for Saorstát Éireann - Mugtaba Osman; Andrew C Parnell; MacDara McCauley (Epidemiology, Biostatistics and Public Health)
Introduction: Emile Durkheim differentiated between two types of wars: National and Civil Wars in terms of effect on suicide mortality. This study investigates Durkheim’s assertion by examining the effect of Irish Civil War on the 1882-1928 suicide rates trend.